Mental health in adolescents with a history of developmental language disorder: The moderating effect of bullying victimisation. (December 2019) - Kilpatrick, Tina; Leitão, Suze; Boyes, Mark
Background: Children and adolescents with a history of developmental language disorder are at elevated risk of experiencing internalising and externalising symptoms. The existing literature suggests a link between developmental language disorder, bullying victimisation and low self-esteem, both of which are negatively associated with child and adolescent mental health more generally. Aim: We examined the relationship between having a history of developmental language disorder and internalising and externalising symptoms in adolescence. We also tested whether bullying victimisation and self-esteem were associated with mental health outcomes, and whether they moderated the association between a history of developmental language disorder and psychological symptoms. Methods and procedures: Adolescents with a history of developmental language disorder ( n =  20, 10–16 years, 10% female, 90% male) were compared to a group of typically developing peers ( n  =   22, 10–16 years, 36.4% female, 63.6% male). Receptive and expressive language, internalising and externalising symptoms, bullying victimisation and self-esteem were assessed with well-validated measures. Outcomes and results: Contrary to our predictions, a history of developmental language disorder was not directly associated with internalising or externalising symptoms. However, in terms of internalising symptoms, there was a significant interaction between a history of developmental language disorder and bullying victimisation ( β  = 1.01, p  =   .02). Specifically, there was a significant association between a history of developmental language disorder and internalising symptoms at high levels of bullying victimisation [ t (41) = 2.52, p  =   .02] but not at low levels of bullying victimisation [ t (41) = –.67, p  =   .51). Conclusions and implications: Bullying victimisation appears to increase the risk of internalising symptoms in adolescents with a history of developmental language disorder. Future research should examine whether anti-bullying interventions can help prevent the development of internalising problems for children with developmental language disorder. These findings may aid clinicians in developing their understanding of developmental language disorder and reinforces the importance of holistic client management in speech language therapy.